Analysis of Traditional Chinese Medicine Syndromes and Treatment Laws of Diabetic Kidney Disease and the Action Mechanism of High-Frequency Chinese Herbs in the Treatment of Diabetic Kidney Disease Based on Real-World Study - Ji, Keyi; Li, Genlin; Wu, Suhui; Yuan, Jiayao; Du, Zheng; Li, Hanbing; Xu, Jiangyan (Chinese medicine and natural products, 2022)
Objective Our objective was to analyze the traditional Chinese medicine (TCM) syndrome and treatment laws of diabetic kidney disease (DKD) and the action mechanism of high-frequency Chinese herbs in the treatment of DKD based on real-world study.Methods The data of patients with DKD who had been treated in the First Hospital Affiliated to Henan University of Chinese Medicine from January 1, 2014 to December 31, 2021 were retrospectively analyzed through the hospital information management system. The contents of the cases were statistically analyzed using IBM SPSS Statistics 25 software, and the laws of DKD treatment were summarized. Network pharmacology and molecular docking were used to analyze the action mechanism of high-frequency Chinese herbs in the treatment of DKD.Results The data of a total of 1,201 patients with DKD were included, involving 72 kinds of TCM syndromes. Nine disease nature elements and six disease location elements were extracted, involving 405 Chinese herbs. The top five high-frequency Chinese herbs were Baizhu (Atractylodis Macrocephalae Rhizoma), Fuling (Poria), Huangqi (Astragali Radix), Chuanxiong (Chuanxiong Rhizoma), and Danshen (Salviae Miltiorrhizae Radix et Rhizoma). Thirty kinds of Chinese herbs with the frequency of ≥100 were mainly deficiency-tonifying herbs and blood-activating and stasis-eliminating herbs. The medicinal properties were mainly warm and mild, and the medicinal flavors were sweet and bitter mostly. For the meridian tropism, the main meridian tropism of these herbs is spleen meridian and lung meridian. The clustering method aggregated the 30 commonly used Chinese herbs into six categories. A total of 58 effective active ingredients of high-frequency Chinese herbs and 164 related targets were screened based on the traditional Chinese medicine systems pharmacology database and analysis platform (TCMSP); 1,434 targets of DKD and 90 potential targets of high-frequency Chinese herbs for DKD were obtained. “Active ingredient-potential target” network topology analysis indicated that quercetin, luteolin, 7-O-methylisoxitol, hederagenin, and 4-methylene miltirone were the five core chemical components of high-frequency Chinese herbs in the treatment of DKD. Protein–protein interaction network topology analysis indicated that protein kinase B1, interleukin-6, tumor necrosis factor, vascular endothelial growth factor A, tumor protein P53 were the core protein targets. Twenty signaling pathways were obtained by Kyoto Encyclopedia of Genes and Genomes enrichment analysis. Molecular docking showed that luteolin, 4-methylene miltirone, and osthole had strong binding to AKT1.Conclusion The differentiation and treatment of DKD with TCM follows the principles of “taking kidney as the root, considering both the liver and spleen, tonifying qi and nourishing yin, promoting blood circulation and resolving blood stasis.” High-frequency Chinese herbs for the treatment of DKD have multicomponent, multitarget, and multipath characteristics.
Keywords: diabetic kidney disease; laws of syndromes and treatment; high-frequency Chinese Herbs; real-world study; TCM; network pharmacology; molecular docking; diabetes mellitus; action mechanism